Determinants of Digital Entrepreneurship Success and Innovative Business Models in East Java Technology Startups - Ninda Rachmawati; Erivina Lucy Kristia (JOURNAL KOPERASI DAN MANAJEMEN, 2026)
Purpose – This study aims to investigate the determinants of digital entrepreneurship success and the adoption of innovative business models among technology startups in East Java, Indonesia. Specifically, it examines the effects of entrepreneurial insight, market orientation, digital infrastructure adoption, and digital platform utilization on startup survival and performance, while assessing the moderating roles of business incubation support and the collaborative Penta Helix entrepreneurial ecosystem. Design/methodology/approach – This study employed a quantitative research design using a structured questionnaire administered to 250 founders and key decision-makers of registered technology startups in East Java. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized direct relationships and the moderating effects of business incubation support and the Penta Helix entrepreneurial ecosystem. Findings – The findings indicate that entrepreneurial insight, market orientation, digital infrastructure adoption, including QRIS and digital banking, and effective utilization of digital platforms such as marketplaces have significant positive effects on startup survival and performance. Furthermore, business incubation support and a collaborative Penta Helix entrepreneurial ecosystem positively moderate these relationships, indicating that supportive institutional and collaborative environments strengthen the ability of startups to transform entrepreneurial capabilities and digital resources into sustainable business outcomes. Research limitations/implications – This study is limited to technology startups in East Java and uses cross-sectional data, which may limit the generalizability of the findings and the ability to capture changes in startup performance over time. Future research could employ longitudinal approaches and examine additional factors such as digital skills, access to venture capital, technological innovation, entrepreneurial resilience, and regulatory support. Originality/value – This study contributes to the digital entrepreneurship literature by developing and empirically validating an integrated model of startup success that combines entrepreneurial capabilities, market orientation, digital infrastructure, platform utilization, and ecosystem support. Its originality lies in examining these relationships within the emerging technology startup ecosystem of East Java and incorporating business incubation and the Penta Helix model as contextual moderators.